Acute supplementation of N‐acetylcysteine does not affect muscle blood flow and oxygenation characteristics during handgrip exercise. Issue 7 (6th April 2016) - Smith, Joshua R.; Broxterman, Ryan M.; Ade, Carl J.; Evans, Kara K.; Kurti, Stephanie P.; Hammer, Shane M.; Barstow, Thomas J.; Harms, Craig A.
Abstract: N ‐acetylcysteine (NAC; antioxidant and thiol donor) supplementation has improved exercise performance and delayed fatigue, but the underlying mechanisms are unknown. One possibility is NAC supplementation increases limb blood flow during severe‐intensity exercise. The purpose was to determine if NAC supplementation affected exercising arm blood flow and muscle oxygenation characteristics. We hypothesized that NAC would lead to higher limb blood flow and lower muscle deoxygenation characteristics during severe‐intensity exercise. Eight healthy nonendurance trained men (21.8 ± 1.2 years) were recruited and completed two constant power handgrip exercise tests at 80% peak power until exhaustion. Subjects orally consumed either placebo (PLA) or NAC (70 mg/kg) 60 min prior to handgrip exercise. Immediately prior to exercise, venous blood samples were collected for determination of plasma redox balance. Brachial artery blood flow (BABF) was measured via Doppler ultrasound and flexor digitorum superficialis oxygenation characteristics were measured via near‐infrared spectroscopy. Following NAC supplementaiton, plasma cysteine (NAC: 47.2 ± 20.3  μ mol/L vs. PLA: 9.6 ± 1.2  μ mol/L; P  = 0.001) and total cysteine (NAC: 156.2 ± 33.9  μ mol/L vs. PLA: 132.2 ± 16.3  μ mol/L; P  = 0.048) increased. Time to exhaustion was not significantly different ( P  = 0.55) between NAC (473.0 ± 62.1 sec) and PLA (438.7 ± 58.1 sec). Resting BABF was not different ( P  = 0.79) with NAC (99.3 ± 31.1 mL/min) and PLA (108.3 ± 46.0 mL/min). BABF was not different ( P  = 0.42) during exercise or at end‐exercise (NAC: 413 ± 109 mL/min; PLA: 445 ± 147 mL/min). Deoxy‐[hemoglobin+myoglobin] and total‐[hemoglobin+myoglobin] were not significantly different ( P  = 0.73 and P  = 0.54, respectively) at rest or during exercise between conditions. We conclude that acute NAC supplementation does not alter oxygen delivery during exercise in men. Abstract : N ‐acetylcysteine, an antioxidant and thiol donor, may improve blood flow during severe‐intensity exercise. In the present study, N ‐acetylcysteine supplementation did not alter blood flow or muscle oxygenation characteristics during severe‐intensity exercise in healthy men.